Factors Influencing Total Productive Maintenance Implementation for Thermal Generation Plants - Danguche, Issa H.; Taifa, Ismail W. R. (Tanzania Journal of Engineering and Technology, 2025)
This study accepts that the technical and administrative factors can amplify effective total productive maintenance (TPM) implementation at thermal generation plants. It is noted that there is a limited number of studies that have attempted to understand the subject of TPM implementation in the energy sector. Noting this shortcoming, the authors thought it crucial to generate empirical evidence on the factors influencing effective TPM implementation for thermal generation plants, with evidence from gas-fired plants. A sample of 88 respondents was selected and consulted. Data were collected through questionnaires and analyzed quantitatively by inferential statistics and qualitatively through thematic analysis using SPSS version 20.0. Confirmatory factor analysis (CFA) was performed through LISREL software version 8.0. On inferential analysis, correlation, regression and ANOVA were performed. Multiple regression analysis results indicate that administrative factors, including management support, TPM awareness, employee participation and strategic planning, positively and significantly influence TPM implementation. Also, technical factors comprising planned maintenance, autonomous maintenance, quality maintenance and early equipment management positively influence TPM implementation at thermal generation plants. The correlation coefficient for all factors was at least 0.6, and the p-value was less than 0.05, suggesting that the study’s independent variables reliably predict the dependent variable. The additional factors influencing TPM implementation include training and education, organization of the workplace, root cause analysis and continuous improvement. From this juncture, the study concludes that effective TPM implementation in the energy sector, especially at thermal generation plants, can be accomplished if many administrative and technical factors are considered. These factors comprise management support, TPM awareness, strategic planning, employee participation, workplace organization, training and education, planned maintenance, autonomous maintenance, quality maintenance, early equipment management, continuous improvement and root cause analysis.